1998
DOI: 10.1159/000030258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Testicular Volumes before and after Varicocelectomy

Abstract: We attempted to determine the testicular volume changes in patients with unilateral varicocele, before and after varicocelectomy. Testicular volume differences were correlated for each group of varicocele grade. 123 men with a unilateral left varicocele were presented for surgery: 36 had grade I, 49 had grade II, and 38 had grade III varicoceles. A Prader orchidometer was used for testicular volume determination before and after varicocelectomy in each patient. Both left and right testicular volumes were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…In contrast, approximately one-third of the infertile men had a clinical varicocele, and the relationship between clinical varicoceles and ipsilateral testicular hypotrophy has also been described (9)(10)(11)(12). Moreover, testicular volumes may increase after varicocele repair with and without improvement of semen parameters (13)(14)(15)(16)(17). Therefore, varicoceles may influence the relationship between testicular volume and testicular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, approximately one-third of the infertile men had a clinical varicocele, and the relationship between clinical varicoceles and ipsilateral testicular hypotrophy has also been described (9)(10)(11)(12). Moreover, testicular volumes may increase after varicocele repair with and without improvement of semen parameters (13)(14)(15)(16)(17). Therefore, varicoceles may influence the relationship between testicular volume and testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical varicocele may be associated with relative ipsilateral testicular hypotrophy compared with the contralateral testis in adulthood (9)(10)(11)(12). Repair of varicocele may be associated with increased testicular volume (13)(14)(15)(16)(17). Therefore, the clinical varicocele may influence the testicular volume-function relationship.…”
mentioning
confidence: 99%
“…Kass and Belman [30] demonstrated that 80% of patients with clinical varicoceles of grades II and III would have hypertrophy of the ipsilateral testis following varicocele surgery with an average follow-up of 3.3 years. This has also been studied by Culha et al [31] who showed that both the ipsilateral and contralateral testicular volumes increased significantly after operation in patients with grade II and III varicoceles. The right testicular volume showed more improvement than the left in the majority of patients [31] .…”
Section: Failure Of Testicular Growth and Developmentmentioning
confidence: 60%
“…This has also been studied by Culha et al [31] who showed that both the ipsilateral and contralateral testicular volumes increased significantly after operation in patients with grade II and III varicoceles. The right testicular volume showed more improvement than the left in the majority of patients [31] . This has further been proved by Yamamoto et al [32] in their study.…”
Section: Failure Of Testicular Growth and Developmentmentioning
confidence: 60%
“…The negative impact of varicocele on testicular size had been shown decades ago in both adolescents and adult males depending on its clinical grade [8][9][10][11]. Zini et al [12] showed that clinical left varicocele can negatively impact left testicular size and that subclinical varicocele is associated with decreased left testicular size.…”
Section: Introductionmentioning
confidence: 99%